2019
DOI: 10.1016/j.scib.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from 2D metal to 3D Dirac semimetal in metallic PtTe2 films with local Rashba effect

Abstract: PtTe 2 and PtSe 2 with trigonal structure have attracted extensive research interests since the discovery of type-II Dirac fermions in the bulk crystals. The evolution of the electronic structure from bulk 3D topological semimetal to 2D atomic thin films is an important scientific question. While a transition from 3D type-II Dirac semimetal in the bulk to 2D semiconductor in monolayer (ML) film has been reported for PtSe 2 , so far the evolution of electronic structure of atomically thin PtTe 2 films still rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 29 publications
4
43
1
Order By: Relevance
“…The interface between PtTe 2 and Py might play a role through the Rashba–Edelstein effect. [ 28 ] However, in that case, a significant field‐like torque [ 47 ] and a negative ξ SOT would appear, [ 25 ] which is in contradiction with our observation. It was reported in Bi x Se 1‐x nanocrystalline thin films that the enhanced ξ SOT can be ascribed to the quantum confinement effect from tiny crystal grains (≈6 nm).…”
Section: Figurecontrasting
confidence: 96%
See 1 more Smart Citation
“…The interface between PtTe 2 and Py might play a role through the Rashba–Edelstein effect. [ 28 ] However, in that case, a significant field‐like torque [ 47 ] and a negative ξ SOT would appear, [ 25 ] which is in contradiction with our observation. It was reported in Bi x Se 1‐x nanocrystalline thin films that the enhanced ξ SOT can be ascribed to the quantum confinement effect from tiny crystal grains (≈6 nm).…”
Section: Figurecontrasting
confidence: 96%
“…Moreover, the helical spin textures at the Fermi level was observed in few‐layer PtTe 2 and ascribed to the local Rashba effect. [ 28 ] Motivated by these intriguing properties, the potential of PtTe 2 in SOT device applications calls for further investigation.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, the energy level of the VBM exceeds that of the CBM, even using the GGA-1/2 technique, leading to an overlap of bands; hence, a semimetal-to-semiconductor transition occurs in this material due to quantum confinement. This is consistent with angle-resolved photoemission studies that have shown BL PtTe 2 to be metallic 34 . The band overlap increases even further for bulk PtTe 2 as shown in Fig.…”
Section: Electronic Structure Of Pttesupporting
confidence: 91%
“…Careful classification and characterization of these defects can allow us to understand their impact on the electronic properties of the intrinsic materials and assess their significance with a view to potential applications. The crystal structure of PtTe 2 has been characterized by transmission electron microscopy (TEM) in several experimental studies 19,21,34 . Although TEM can routinely resolve the atomic structure of materials, it cannot provide easy access to the electronic band structure around the Fermi level of individual point defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evolution of electronic structure of atomically thin PtTe 2 films still remains elusive. Zhou's group [11] from Tsinghua University has revealed that the PtTe 2 film evolves from a 2D metallic at 2 ML to a 3D Dirac semimetal at 4-6 ML thickness based on the angle-resolved photoemission spectroscopy (ARPES). The helical spin texture induced by the local Rashba effect in bulk PtTe 2 was reported in the meanwhile.…”
Section: Qihua Xiongmentioning
confidence: 99%